2018
DOI: 10.1111/ejn.14194
|View full text |Cite
|
Sign up to set email alerts
|

Testing the role of the posterior cingulate cortex in processing salient stimuli in cannabis users: an rTMS study

Abstract: The posterior cingulate cortex (PCC) and precuneus are hubs in the default mode network and play a role in processing external salient stimuli. Accordingly, activation in these regions has been associated with response to salient stimuli using drug cue‐reactivity paradigms in substance using populations. These studies suggest that the PCC and precuneus may underlie deficits in processing salient stimuli that contribute toward the development of substance use disorders. The goal of this study was to directly te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…Based on these observations a recent study employed transcranial stimulation (TMS) to this region during cueinduced reactivity in substance addiction and demonstrated that down-regulation of this region normalized exaggerated self-referential attribution in cannabis-dependent subjects. 44 In the context of these previous findings the convergent cross sectional is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) preprint…”
Section: Discussionmentioning
confidence: 99%
“…Based on these observations a recent study employed transcranial stimulation (TMS) to this region during cueinduced reactivity in substance addiction and demonstrated that down-regulation of this region normalized exaggerated self-referential attribution in cannabis-dependent subjects. 44 In the context of these previous findings the convergent cross sectional is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) preprint…”
Section: Discussionmentioning
confidence: 99%
“…engaging different brain regions in these different subgroups). In another double‐blind, placebo‐controlled, cross‐over design, high‐frequency repetitive transcranial magnetic stimulation (rTMS) to the posterior cingulate cortex and cuneus showed normalization of the processing of self‐relevant stimuli (assessed using event‐related potential P3 amplitudes and P3, N2 and P2 latencies) in cannabis users as compared with non‐users (Prashad et al ., ). Thus, in addition to pharmacological approaches in combination with magnetic resonance imaging to measure outcomes, brain stimulation and EEG recordings expand the toolbox available to clinicians in treating addiction.…”
Section: Human Studiesmentioning
confidence: 97%
“…In contrast to other SUDs, however, very little research has been conducted on the efficacy of TMS as a tool for cannabis use disorder. The first experimental study was a double-blind crossover study that evaluated the effect of a single session of TMS on event-related brain reactivity to cues [81]. This was followed by a second experimental study evaluating the feasibility and tolerability of TMS to the left DLPFC in 18 individuals with cannabis use disorder [82].…”
Section: Cannabis Use Disordermentioning
confidence: 99%